Bank Concentration and the Supply of Credit in Argentina - Canonero, Gustavo (IMF Working Papers; Working Paper ;, 1997)
This paper examines the effects on the supply of credit of the concentration of financial institutions in Argentina that followed the crisis caused by the December 1994 devaluation of the Mexican peso. While the concentration process may have improved the efficiency of domestic financial intermediation, the analysis suggests that, due to the presence of information asymmetries in the banking sector, it also may have contributed to the contraction in bank lending observed during 1995.